Pre-online information searching model of doctoral students: A grounded theory approach / Azree Ahmad - Ahmad, Azree (Institute of Graduate Studies, UiTM, 2016)
This study was conducted with the purpose of exploring the beginning stage in information searching process. As far as it is concerned, most would agree that information searching is a constructive and evolving process that has several stages. Based on few discoveries, pre-searching was found to have existed much earlier than the actual search or main interaction stage of the information searching process. However, not all users including doctor of philosophy (Ph.D.) degree students were successful in the beginning of their information searching. One way to look at this problem is to understand their pre-searching. The importance of pre-searching in information searching is that it has a significant impact on the quality of the search result. During the study, the data gathering activity involved a great length of doctoral students presearching experiences which were obtained through semi-structured interview sessions. The selection of twenty three doctoral students as participants started with purposive sampling which was used to draw the first participant, while subsequent participants were selected based on theoretical sampling. Data was later transcribed and interpreted according to the coding paradigm of the grounded theory approach where emerging concepts were identified, arranged, linked and presented in a meaningful way…